A comparative study on the impact of media viewing on early childhood of typically developing children and children with autism - Anubhooti Nagar; Madhumita James; Sah V P (Journal of All India Institute of Speech and Hearing, 2013)
With few literature reviews available in India over the effects of media exposure on children, a study was required to appraise the effects of media and timing of its exposure. A standard & validated questionnaire (adapted from the study of Rideout V.J. et al, 2003) was used in the survey to collect information from the parents (fluent in English) of 30 typically developing children and 25 autistic children between 3-6 years of age. In the first phase of data collection adaptation of the questionnaire to our cultural context and life-style was done. Second phase included collection of primary data through non probability sampling. A detailed history of the child with language assessment (REELS, Bzoch & League, 1971) was taken. Additional CARS (Schopler et al, 1966) was administered on children with autism. On SPSS(V_12.0) a significant difference ( p< 0.05) was found between the autistics and typically developing children in terms of receptive (t=9.033) and expressive (t=10.230) language age. Results revealed on an average child with autism were exposed to electronic media for 15.7 hours and typically developing children for 17.4 hours per week. Longer duration with unhealthy quality of viewing was seen in children (30.9%) belonging to low socioeconomic status and less educated parents. 64% parents of autistic and 56% parents of typically developing children stated that exposure to educational television shows mostly helps the children in intellectual development. According to parents either a positive or a negative behavioral modification was observed in children of both groups after being exposed to the electronic media. In conclusion, this paper highlights the need to assess the unfathomable intrusion of technology and its prospective effect in the life of children these days. The effects are detrimental and exposure to electronic media should be taken into consideration when assessing children with delayed or deviant language or any other behavioral problems. Better understanding of the amount and type of exposure will have scientific implications in terms of how the early environment of a child should be structured.